Forest trees filter chronic wind‐signals to acclimate to high winds. Issue 3 (21st January 2016) - Bonnesoeur, Vivien; Constant, Thiéry; Moulia, Bruno; Fournier, Meriem
Summary: Controlled experiments have shown that trees acclimate thigmomorphogenetically to wind‐loads by sensing their deformation (strain). However, the strain regime in nature is exposed to a full spectrum of winds. We hypothesized that trees avoid overreacting by responding only to winds which bring information on local climate and/or wind exposure. Additionally, competition for light dependent on tree social status also likely affects thigmomorphogenesis. We monitored and manipulated quantitatively the strain regimes of 15 pairs of beech ( Fagus sylvatica ) trees of contrasting social status in an acclimated stand, and quantified the effects of these regimes on the radial growth over a vegetative season. Trees exposed to artificial bending, the intensity of which corresponds to the strongest wind‐induced strains, enhanced their secondary growth by at least 80%. Surprisingly, this reaction was even greater – relatively – for suppressed trees than for dominant ones. Acclimated trees did not sense the different types of wind events in the same way. Daily wind speed peaks due to thermal winds were filtered out. Thigmomorphogenesis was therefore driven by intense storms. Thigmomorphogenesis is also likely to be involved in determining social status.